Wastewater treatment in flow photobioreactors continuous illuminated by artificial and solar light (Research, Society and Development, 2020)
The technology of microalgae photobioreactors and illuminated by LEDs has been widely studied for the treatment of wastewater. However, sunlight is a free resource and should be taken advantage of. But the question remains whether photobioreactors illuminated by natural (sunlight) light in combination with artificial light can have greater operational stability or greater performance when compared to systems illuminated only by artificial light. In this context, continuous flow photobioreactors illuminated by Light Emitting Diodes (LEDs) combined, or not, with sunlight were operated and had their performance evaluated. The variables analyzed were pH, OD, chemical oxygen demand (COD), chlorophyll - a and total suspended solids. The photobioreactors were effective for removing organic matter, with 75 ± 15% in the photobioreactor illuminated by LED and 65 ± 10% in the photobioreactor illuminated by sunlight and LED. The results showed that the use of combined lighting favors the production of dissolved oxygen and ensures greater operational stability in the removal of carbonaceous organic matter.